Implementasi Pembelajaran Diferensiasi Pada Mata Pelajaran PPKn Di SMP Negeri 9 Kota Serang - Wika Hardika Legiani; Siti Rohmah; Siti Mita Mutaminah; Sera Nurlita; Ilwan Aliansah (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Citizenship education is a compulsory education for citizens, starting from elementary, middle, high school to university or college level. Civic education plays an important role in the process of learning citizens to become smart and good citizens. Differentiated learning is learning that helps students' learning needs. Teachers facilitate students according to their needs, because each individual student has very different characteristics, so they cannot be given the same treatment. Teachers facilitate students according to their needs, because each student has different characteristics, so they are not given the same treatment in the learning process. In implementing differentiated learning, teachers must prepare learning with a variety of different treatments and actions for each learner. The purpose of this study was to determine the implementation of differentiated learning in Civics subjects at SMP Negeri 9 Serang City. The method used in this research is to use qualitative methods that are descriptive in nature. Data collection techniques in this study are using interview techniques, observation, and documentation. The results of this study are process differentiation refers to the way teachers invite students to enter into learning activities and discover their knowledge independently in the process. Teachers are required to prepare triggering questions, interesting and challenging materials so that students enjoy the process presented by the teacher. The characteristic of differentiated learning is a conducive learning environment that meets the needs of learners.